2017
DOI: 10.1002/wat2.1226
|View full text |Cite
|
Sign up to set email alerts
|

Picturing waters: a review of Photovoice and similar participatory visual research on water governance

Abstract: Seeing is one of the main sensory experiences for knowing water and for generating meanings of it. To acknowledge this, visual research methods are increasingly popular in social sciences. In this paper, research using Photovoice or similar participatory visual methods is reviewed in order to assess their potential contribution to the study of water governance. A total of 23 articles related to 20 projects on (1) water, health, and sanitation; (2) participation in water management; (3) landscapes and water spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 34 publications
(20 reference statements)
0
29
0
Order By: Relevance
“…Among women, Photovoice has been used in Usoma, a lakeshore community in Western Kenya (Bisung et al 2015a;Bisung et al 2015b) and with Dar es Salaam mothers in Tanzania (Badowski et al 2011) to explore the nexus of water and health in relation to unsafe water and inadequate sanitation. Issues of water governance have been assessed through Photovoice (Fantini 2017), as well as the gendered nature of water in Sierra Leone concerning the use of water and water infrastructure (Thompson 2011). These studies illustrate that Photovoice is a viable method to research water and sanitation issues in water insecure communities.…”
Section: Global Photovoice Literaturementioning
confidence: 99%
“…Among women, Photovoice has been used in Usoma, a lakeshore community in Western Kenya (Bisung et al 2015a;Bisung et al 2015b) and with Dar es Salaam mothers in Tanzania (Badowski et al 2011) to explore the nexus of water and health in relation to unsafe water and inadequate sanitation. Issues of water governance have been assessed through Photovoice (Fantini 2017), as well as the gendered nature of water in Sierra Leone concerning the use of water and water infrastructure (Thompson 2011). These studies illustrate that Photovoice is a viable method to research water and sanitation issues in water insecure communities.…”
Section: Global Photovoice Literaturementioning
confidence: 99%
“…Recent review articles on the use of different art-based methods in environmental and health research found that most artbased research is carried out in the United States, Canada, the United Kingdom and France (Nurmis, 2016;Galafassi et al, 2018;Coemans and Hannes, 2017). Research on arts and health is often also done in Africa (Teti et al, 2018) and water-related creative practice research is concentrated in water-scarce regions in Africa and Australia (Fantini, 2017). In this study, we searched for papers focusing on Global South and vulnerable communities.…”
mentioning
confidence: 99%
“…Beh et al, 2013), water use and governance (e.g. Fantini, 2017;Bisung et al, 2015), and hazards and disasters (e.g. Yoshihama and Yunomae, 2018;Schumann et al, 2018).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Further, following decades of anthropologists' engagement with visual research, videography, participatory video (PV), and photo elicitation are becoming increasingly popular (Fantini, 2017;Garrett, 2010;Latham, 2003;Pink, 2008Pink, , 2010Pink, , 2012Rose, 2016). In water research, spatial video has been used to explore the relationship between space, distance, body and access to water (Smiley et al, 2017) and photo elicitation to promote ways of knowing based on seeing, "one of the main sensory experiences for knowing water" (Fantini, 2017, p. 1).…”
mentioning
confidence: 99%